The Mind: Discipleship that Forms the Thoughts of Christians—Reflections on Dallas Willard's Thinking on the Mind (Thoughts). Issue 1 (April 2019) - Yount, Rick
Renovation of the heart presents Dallas Willard's vision for spiritual (trans)formation. He defines six essential components of human existence: Will/Heart/Spirit, the Mind (Thoughts) and Mind (Feelings), the Body, the Social, and the Soul, which organizes components into a single person. This article analyzes Willard's view of Mind (Thoughts), the rational and most important component of personhood, for spiritual growth. Implications of ideas, images, information, and the ability to think are made in connection with life-long, intentional, and consistent discipleship. Willard's biblical/philosophical approach to formation is contrasted with Christian educators' biblical/psychological approaches. Finally, nine applications of Willard's conception of Mind (Thoughts) are defined and illustrated for use in the provision of practical opportunities for spiritual formation from local churches, to seminary classrooms, to mission stations around the world.